Thought leadership and international new ventures’ brand awareness - Peltonen, Emma (fi=Turun yliopisto|en=University of Turku|, 2018)
The digital disruption and globalization have opened up opportunities to international new ventures like never before and the chances to scale quickly to the international markets are better than ever. However, the international new ventures lack identity and reputation, they have a limited budget to establish their brand and they are still missing a customer base. There are earlier studies on how to build and enhance brand awareness in consumer markets but from B2B perspective, there is little empirical evidence from the academia on the strategies of how to build and develop a brand in a business-growth friendly way. Hence, for a new venture to create brand awareness, this study suggests aiming for the position of a thought leader. The purpose of this study was to investigate how thought leadership would support brand awareness of an international new venture. To support the main research problem, two sub-objectives were to: • identify the characteristics that make a company a thought leader • explore how international new venture can create brand awareness In this study, the data was collected through exploratory expert interviews. There were five interviews altogether, out of which four were conducted with companies who actively pursue thought leadership strategy. The fifth interviewee was the founder of a start-up consulting firm that brings together more established businesses and start-ups. The main findings of the empirical research are in line with the theoretical framework of the thesis. In the light of this study, it appears that thought leadership would create brand awareness by attracting interest from stakeholders such as media and customers, because a thought leading company has something new and meaningful to say. Furthermore, both public relations and customers telling the company story seem to enhance the firm’s halo and thus, its credibility. However, in order to reach the minds of journalists and customers, the company must conduct activities, such as attending events, publishing relevant content and sharing on social media, to create awareness. Hence, there is a slight dilemma whether thought leadership is supporting brand awareness, or is the brand awareness needed in order to become a thought leader. It appears to be a cycle: thought leadership increases brand awareness and the increased brand awareness further strengthens the thought leadership positioning. One key finding was also that an INV does not need to become a thought leader in the minds of all the targeted audiences at once, but it can communicate its thought leadership to different audiences in a suitable order. Based on the results, INVs should aim to become thought leaders in their field and increase their brand awareness in this way.